Metode Presentasi untuk Meningkatkan Aktivitas Belajar Teknologi Sederhana pada Siswa Kelas B Taman Kanak-kanak Kartika II-31 Bandar Lampung - Ayuda, Siti (Lentera: Jurnal Ilmiah Kependidikan, 2020)
The research objective is to increase the activity and learning achievement of Simple Technology by applying the Presentation Method to students of the Class BTK Kartika II-31 Bandar Lampung in 2019. The research method uses Classroom Action Research (Self Reflective Inquiry) which is carried out in three research cycles through the stages of planning, implementation. , observation and reflection. The implementation of 3 cycles and 3 meetings every cycle from January to April 2019. The results of the Cycle I study of learning outcomes averaged 63 with the category Enough, Complete 63%. In cycle II, the average learning result is 74 with Good category, Completed 83%. In Cycle III, the average learning outcome was 86 with the very good category, 96% complete. Learning activity in Cycle I was 63% active, Cycle II was 83% active and Cycle III was active 96%. Observer observations about teacher performance in learning average in good category. Thus, the application of the presentation method can increase the activity and achievement of simple technology learning in class B students at TK Kartika II-31 Bandar Lampung.